Using Web Services for Linking Genomic Data to Medical Information Systems - Maojo, V.; Crespo, J.; Calle, G. de la; Barreiro, J.; Garcia-Remesal, M. (Methods of Information in Medicine, 2007)
Objectives: To develop a new perspective for biomedical information systems, regarding the introduction of ideas, methods and tools related to the new scenario of genomic medicine.Methods: Technological aspects related to the analysis and integration of heterogeneous clinical and genomic data include mapping clinical and genetic concepts, potential future standards or the development of integrated biomedical ontologies. In this clinicomics scenario, we describe the use of Web services technologies to improve access to and integrate different information sources. We give a concrete example of the use of Web services technologies: the Onto Fusion project.Results: Web services provide new biomedical informatics (BMI) approaches related to genomic medicine. Customized workflowswill aid research tasks by linking heterogeneous Web services. Two significant examples of these European Commission-funded efforts are the INFOBIOMED Network of Excellence and the Advancing Clinico-Genomic Trials on Cancer (ACGT) integrated project.Conclusions: Supplying medical researchers and practitioners with omicsdata and biologists with clinical datasets can help to develop genomic medicine. BMI is contributing by providing the informatics methods and technological infrastructure needed for these collaborative efforts.
Keywords: Biomedical informatics; Web services; genomic medicine; hospital information systems